2011
DOI: 10.1002/chem.201100972
|View full text |Cite
|
Sign up to set email alerts
|

Dopant Segregation Analysis on Sb:SnO2 Nanocrystals

Abstract: The development of reliable nanostructured devices is intrinsically dependent on the description and manipulation of materials’ properties at the atomic scale. Consequently, several technological advances are dependent on improvements in the characterization techniques and in the models used to describe the properties of nanosized materials as a function of the synthesis parameters. The evaluation of doping element distributions in nanocrystals is directly linked to fundamental aspects that define the properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 33 publications
1
24
0
1
Order By: Relevance
“…With increasing reaction times, surface diffusion promoted mass transportation towards the tips of the rods, resulting in dumbbell‐like morphologies, which then fragmented by a detachment process into well‐faceted nanoparticles (Figure b). Also antimony‐doped tin oxide (ATO) nanocrystals synthesized by the benzyl alcohol route present an oriented attachment growth mechanism . In that report, the authors showed that the combined use of surface energy ab initio calculations and Wulff construction could be applied to study the oriented attachment configurations.…”
Section: Crystallization Mechanismsmentioning
confidence: 99%
“…With increasing reaction times, surface diffusion promoted mass transportation towards the tips of the rods, resulting in dumbbell‐like morphologies, which then fragmented by a detachment process into well‐faceted nanoparticles (Figure b). Also antimony‐doped tin oxide (ATO) nanocrystals synthesized by the benzyl alcohol route present an oriented attachment growth mechanism . In that report, the authors showed that the combined use of surface energy ab initio calculations and Wulff construction could be applied to study the oriented attachment configurations.…”
Section: Crystallization Mechanismsmentioning
confidence: 99%
“…Furthermore, the shape and the exposed surface planes can be estimated on the base of projected two-dimensional HRTEM images. Stroppa et al [97] evaluated the three dimensional morphology of Sb doped SnO 2 nanocrystals by combined use of experimental HRTEM image, multislice simulated HRTEM images,…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…[68,69] Apart from HRSTEM tomography [24] and reconstruction of the HAADF-HRSTEM images based on the recorded intensities, [23,25] scanning confocal electron microscopy (SCEM) on STEM mode is a suitable technique for extracting structural information along the imaging zone axis.…”
Section: Scanning Confocal Electron Microscopymentioning
confidence: 99%